Relationships between technical and physical match performance in elite soccer - Radziminski, L.; Szwarc, A.; Jastrzebski, Z.; Rzeszutko-Belzowska, A. (Baltic Journal of Health and Physical Activity, 2022)
Introduction: The purpose of this study was to investigate the potential associations between physical and technical match performance and to compare these activities in relation to the match outcome. Materials and methods: The research was based on an analysis of 622 matches of the Polish Ekstraklasa during three consecutive seasons. Such variables as total distance, distance covered in different speed zones, effective playing time, ball possession, number of passes and passing accuracy were taken into account. Results: Effective playing time (Et) was significantly and fairly correlated with total distance (r = 0.39, p < 0.001), ball possession (r = 0.50, p < 0.001), number of passes (r = 0.40, p < 0.001), number of accurate passes (r = 0.43, p < 0.001) and passing accuracy (r = 0.42, p < 0.001). The comparison of the match performance according to the game outcome indicated that the total and sprinting distance covered by winning teams were significantly (p < 0.01) longer than in losing teams (113.3 vs 112.7 km). In turn, the defeated teams had significantly greater ball possession (28.3 vs 26.4 mins) and performed a larger number of passes (470 vs 428) than the winning teams. Conclusions: Et is one of the factors influencing the physical and technical match performance. Coaches should be aware that their team will have to cover a longer distance when playing against teams that prefer to keep the ball.